Hubungan Pengetahuan dan Sikap Remaja Putri Dengan Manajemen Kesehatan Menstruasi di Posyandu Remaja Wilayah Kerja Kelurahan Baran Timur - Alifia Nur Anniza; Rachmawaty M. Noer; Yulianti Wulandari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Menstrual health management is a way to maintain cleanliness and health when women are menstruating. Poor knowledge and attitudes can lead to poor menstrual health management which can cause disease in women's reproductive organs. The aim of this research was to determine the relationship between knowledge and attitudes of adolescent girls and menstrual health management in the youth posyandu in the working area of ​​Baran Timur subdistrict. This research is a quantitative research with a cross-sectional approach. The population in this study were teenage girls who had menstruated with a total of 87 respondents taken through total sampling. Data collection used a questionnaire and data analysis used the chi-square test. Bivariate analysis results show a p value of 0.016 for the relationship between knowledge and menstrual health management and a p value of 0.029 for the relationship between attitudes and menstrual health management, where this value is less than 0.05 so that Ha is accepted which means there is a relationship between knowledge and attitudes of young women and menstrual health management. It is hoped that knowledge of menstrual health management will be further improved so that attitudes will improve. The author's suggestion for the Ceria Youth Posyandu is to be able to collaborate with the community health center and the East Baran sub-district to be able to provide education regarding Menstrual Health Management not only to young women but also to young men.